2020
DOI: 10.1111/efp.12658
|View full text |Cite
|
Sign up to set email alerts
|

First report of Calonectria cerciana causing leaf blight of Eucalyptus in northern India

Abstract: Eucalyptus spp. and their hybrids are frequently cloned and mass planted across farmland tracts and commercial plantations in northern India. It is a viable feeder species to the paper and pulp industries in this region. In 2018 and 2019, during field surveys conducted in northern India, a serious leaf blight disease was frequently observed in E. tereticornis plantations. Isolation from the blighted leaf samples consistently yielded fungal isolates having Calonectria‐like morphology. Morphological features cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The molecular details of multiple DNA sequences have been applied in identifying fungal species [ 42 , 43 ]. For instance, Bose et al [ 47 ] used two DNA sequences of tub2 and tef1-α to confirm the species of C . cerciana causing leaf blight of Eucalyptus in northern India.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular details of multiple DNA sequences have been applied in identifying fungal species [ 42 , 43 ]. For instance, Bose et al [ 47 ] used two DNA sequences of tub2 and tef1-α to confirm the species of C . cerciana causing leaf blight of Eucalyptus in northern India.…”
Section: Discussionmentioning
confidence: 99%
“…India has a net planted area of 3.9 million hectares of Eucalyptus, cerciana (Bose et al, 2020;Mohanan, 2014;Mohanty et al, 2012;Old et al, 2003;Rattan et al, 1983;Sharma et al, 1984;Sharma & Mohanan, 1982).…”
Section: Impact Of Calonectria Leaf Blightmentioning
confidence: 99%
“…colhounii ) and Ca. cerciana (Bose et al, 2020; Mohanan, 2014; Mohanan & Sharma, 1984, 1985; Mohanty et al, 2012; Old et al, 2003; Rattan et al, 1983; Sharma et al, 1984; Sharma & Mohanan, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Crous et al (2019) reported the association of 110 different genera including species with foliar disease symptoms of eucalypts and suggested the need for further investigations on their pathogenicity. Recent surveys conducted in northern India identified Calonectria cerciana (Bose et al, 2020), C. pseudoreteaudii (Bose et al, 2022) and Lasiodiplodia iraniensis (Negi et al, 2023) as emerging threats to Eucalyptus trees.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) reported the association of 110 different genera including species with foliar disease symptoms of eucalypts and suggested the need for further investigations on their pathogenicity. Recent surveys conducted in northern India identified Calonectria cerciana (Bose et al., 2020), C. pseudoreteaudii (Bose et al., 2022) and Lasiodiplodia iraniensis (Negi et al., 2023) as emerging threats to Eucalyptus trees. In December 2022, symptoms of a severe leaf spot and blight disease were observed on Eucalyptus camaldulensis trees in Yamunanagar, Haryana, northern India (N 30°13.981″ E 77°21.304″, 278 m amsl).…”
Section: Introductionmentioning
confidence: 99%